Distributed Box Particle Filtering for Target Tracking in Sensor Networks - Ying Liu; Hao Liu (International Journal of Distributed Sensor Networks)
Distributed target tracking is a significant technique and is widely used in many applications. Combined with the interval analysis, box particle filtering (BPF) has been proposed to solve the problem of Bayesian filtering when the uncertainties in the measurements are intervals; that is, the measurements are interval-based vectors. This paper is targeted for extending the existing BPF based on a single sensor to a distributed sensor network. We propose a distributed BPF (d-BPF) that each sensor communicates with its direct neighbors to collaboratively estimate the states of the target. The feasibility of the proposed distributed BPF is justified, and some numerical simulations are presented to show its effectiveness in target tracking.